Species Composition, Life Forms and Biological Spectrum of the Watershed Areas of South Rajasthan - Katewa, S. S.; Sharma, Rajesh (Indian Forester, 1999)
The biological spectrum of protected and grazed watershed areas of South Rajasthan, reveals that the vegetation of this area is Therophytic. Total 98 species were present in the study area. The life forms observed in protected site were Phanerophytes (16.4%), Chamaephytes (3.5%), Cryptophytes (18.8%), Hemicryptophytes (2.4%) and Therophytes (58.8%), while in grazed site were Phanerophytes (3.5%), Chamaephytes (5.3%), Cryptophytes (19.6%), Hemicryptophytes (3.5%) and Therophytes (67.8%). The percentage of Therophytes and Cryptophytes is higher in comparison to Raunkiaer's normal spectrum. The higher percentage of Therophytes in grazed site is due to biotic interferences particularly due to grazing by cattle.